Mycobacterium genavense infections in non-HIV immunocompromised hosts: a systematic review. Issue 5 (4th May 2018) - Mahmood, Maryam; Ajmal, Saira; Abu Saleh, Omar M.; Bryson, Alexandra; Marcelin, Jasmine R.; Wilson, John W.
Abstract: Background: Mycobacterium genavense is a non-tuberculous mycobacterium which can rarely cause disease in non-HIV immunocompromised hosts. We describe our experience with this unusual infection and perform a systematic review of the literature to describe the features of M. genavense infection in non-HIV immunocompromised hosts. Methods: All cases of Mycobacterium genavense infection in non-HIV patients at our institution were reviewed. In addition, we conducted a systematic review of the literature to identify previously published cases of M. genavense infections in non-HIV hosts. Findings: Two cases of M. genavense were identified at our center; a 51-year-old renal transplant recipient with a prosthetic knee joint infection and a 66-year-old woman with idiopathic CD4 lymphocytopenia with gastrointestinal tract disease. The systematic review identified 44 cases of M. genavense infection in non-HIV hosts. The most common underlying conditions were solid organ transplantation (40%), sarcoidosis (14%) and hematopoietic stem cell transplantation (7%). Disease most commonly involved the gastrointestinal tract, spleen, liver or bone marrow. Diagnosis was challenging with PCR required for identification in nearly all cases. Over one-third of patients died, which may reflect the combination of infection and underlying comorbidities. Overall cure was achieved in 61% with a mean duration of antimycobacterial therapy of 15.5 months (range 10–24). Conclusion: M. genavense infection is a rare mycobacterial infection in non-HIV immunocompromised hosts. It should be suspected in immunocompromised patients presenting with disseminated mycobacterial infection, acid fast bacilli on smear or histopathologic examination, with poor or no growth in mycobacterial cultures.